(untitled) (Global Journal of Human-Social Science, 2020)
The relevance of the article is due to the activation of radical nationalist trends under the influence of external actors in the streaming political space. Modern panturkism is a social trend that contributes to the strengthening of interethnic and international socio-cultural ties, but at the same time, panturkism is used by nationalist parties and organizations to exercise a destructive influence on society, attempts to interfere in the internal politics of sovereign states. Archaic symbols used by radical panturkists spread through modern communication channels of information exchange. The author presents the results of a comprehensive analysis of the network communities of radical panturkism of the social network Facebook. It is revealed that at present there is not only an increase in the spread of radical values, but also an increase in anti-Russian and anti-Chinese rhetoric.